2015
DOI: 10.4236/fns.2015.615147
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Epidemiological Study to Estimate Usual Intake and to Define Optimum Nutrient Profiling Choice in the Diet of Egyptian Youths

Abstract: Objectives: To define optimum food and nutrient profiling in gender-specific and age group-specific variant regression models. Setting: 481 subjects of both sexes (18.4 years old) from Giza urban were set. Design: Dietary assessment used the 24-h dietary recall data to calculate the estimated energy and (24) nutrients eaten by each individual. Four indices-food variety diversity score, healthy eating index (HEI), mean probability of nutrients adequacy (MPA) and nutrient rich food (NRF9.3) index score were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
0
3
1
Order By: Relevance
“…A study on 2696 adults from the USA and the UK (32) showed that the NRF index was negatively related to BMI, which was consistent with our findings. And a study in Egyptian youths showed that NRF9•3 index was correlated negatively with markers of abdominal obesity (33) , which was different from our results, while a study consisting of 4969 Dutch participants aging > 55 years reported positive correlation between NRF index score and BMI (34) , WC and WHR (34) . Causative factors for this discrepancy include underreporting of food intake among the obese participants, unique different characteristics of the participants such as race, age, gender and health status; different cut-off points of obesity; different methodologies of statistical analysis and adjustment of possible confounding factors; variation in the definition of some food ingredients such as differentiation between added sugars (32) and total sugars (34) .…”
Section: Discussioncontrasting
confidence: 99%
“…A study on 2696 adults from the USA and the UK (32) showed that the NRF index was negatively related to BMI, which was consistent with our findings. And a study in Egyptian youths showed that NRF9•3 index was correlated negatively with markers of abdominal obesity (33) , which was different from our results, while a study consisting of 4969 Dutch participants aging > 55 years reported positive correlation between NRF index score and BMI (34) , WC and WHR (34) . Causative factors for this discrepancy include underreporting of food intake among the obese participants, unique different characteristics of the participants such as race, age, gender and health status; different cut-off points of obesity; different methodologies of statistical analysis and adjustment of possible confounding factors; variation in the definition of some food ingredients such as differentiation between added sugars (32) and total sugars (34) .…”
Section: Discussioncontrasting
confidence: 99%
“…Several studies have investigated the effect of dietary patterns, anthropometric measurements, or metabolic parameters on inflammatory markers [ 18 , 19 ]. However, the study investigated all these factors in metabolic syndrome population using CRP and NLR as the indicators of inflammation was still rare.…”
Section: Introductionmentioning
confidence: 99%
“…Nutrient-rich foods (NRF) index was a valid tool to assess the nutrient density of individual foods and also to assess the total diet [4,12,13] . Diets with high NRF index score protect against central obesity [14] and higher body mass index (BMI) [4,15] , and was inversely associated with all-cause mortality [16] .…”
Section: Introductionmentioning
confidence: 99%